Improving Responsiveness to Patient Phone Calls - Lisa K O’Brien DO; Patricia Drobnick RN, CNOR; Mary Gehman RN; Christopher Hollenbeak PhD; Mark R Iantosca MD, FAANS; Sherri Luchs RN, BSN, MHA; Maureen Manning RN, MSN; Susan K Palm BSN, BA, RN, CRRN; John Potochny MD; Angela Ritzman; Jennie Tetro-Viozzi; Mary Trauger RN, BS, C-SSBB; et al. (Journal of Patient Experience, 2017)
Optimal patient-physician communication in the outpatient clinical setting is critical for safe and effective patient care. Keeping track of multiple patient telephone messages can be difficult and hazardous if a structured system is not in place. A multidisciplinary group at Hershey Medical Center developed a standardized approach for addressing patient telephone calls at their outpatient surgical clinics. This program was designed to improve the patient experience by providing a realistic time frame for phone calls to be returned and requests fulfilled. Additionally, this system permitted phone calls to be tracked and documented appropriately and allowed for prioritization of urgent and emergent messages. Our intent for this program was to close potential gaps within the communication chain at our outpatient surgical clinics, improve overall communication between clinicians and their patients, and improve both patient and employee satisfaction.